2017
DOI: 10.18869/nrip.irj.15.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cognitive Behavioral Therapy Training in Reducing Depression in Visually Impaired Male Students

Abstract: Objectives: According to the prevalence of psychological problems, especially depression in people with visual impairment, this study aimed at investigating the effectiveness of group training of cognitive behavioral therapy in reducing depression in visually impaired male students. Methods:This study employed a quasi-experimental design, with pre-test and post-test and control group. The study population included 30 students with visual impairment from high school and pre-university levels. The subjects studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
3
2
0
Order By: Relevance
“…The results related to the third hypothesis showed that there were statistically significant differences at the level of 0.05 in the level of social skills and isolation behaviors of the experimental group between the pre-and post-measurement, and in favor of the postmeasurement. The result of this hypothesis agrees with the findings reported by Soleimani Sefat et al [34] and Edward [37] who reported that there are statistically significant differences in the level of social skills and isolation behaviors in favor of the post-measurement.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results related to the third hypothesis showed that there were statistically significant differences at the level of 0.05 in the level of social skills and isolation behaviors of the experimental group between the pre-and post-measurement, and in favor of the postmeasurement. The result of this hypothesis agrees with the findings reported by Soleimani Sefat et al [34] and Edward [37] who reported that there are statistically significant differences in the level of social skills and isolation behaviors in favor of the post-measurement.…”
Section: Discussionsupporting
confidence: 92%
“…The results related to the second hypothesis showed that there were statistically significant differences at the significance level (α ≤ 0.05) between the experimental group and the control group in the level of social skills and the isolation behaviors of the study individuals on the post-measurement, and in favor of the experimental group, and thus the result of this hypothesis agrees with the findings reported by Soleimani Sefat et al [34] and Siahkalroudi & Bahr [36] who reported the effectiveness of cognitive behavioral therapy in improving the level of social skills and reducing isolation behaviors among the participants, as these studies were interested in examining the performance of members of the groups after the counseling intervention.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the CBT improved social competence among physically disabled adolescents, so that after CBT, social competence significantly improved in the intervention group compared to the controls. This finding is in agreement with the results of similar studies conducted in this field [22][23][24][25]. Momeni et al reported the positive impact of life skills training on enhancement of social and emotional competence in students [22].…”
Section: Discussionsupporting
confidence: 92%
“…One of the most effective treatments in the psychological field is cognitive behavioral therapy (CBT) [25]. CBT group interventions and counseling have been reported to improve mental health in the visually impaired [26][27]. Recently, it has been shown that CBT with Nurse-led intervention improved depression symptoms [28][29].…”
Section: Services Humanmentioning
confidence: 99%